2019
DOI: 10.3899/jrheum.180445
|View full text |Cite
|
Sign up to set email alerts
|

Economic Burden among Commercially Insured Patients with Systemic Sclerosis in the United States

Abstract: Objective.To quantify healthcare resource utilization (HRU), work loss, and annual direct and indirect healthcare costs among patients with systemic sclerosis (SSc) compared to matched controls in the United States.Methods.Data were obtained from a large US commercial claims database. Patients were ≥ 18 years old at the index date (first SSc diagnosis) and had ≥ 1 SSc diagnosis in the inpatient (IP) or emergency room (ER) setting, or ≥ 2 SSc diagnoses on 2 different dates in the outpatient (OP) setting between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
5
13
0
Order By: Relevance
“…We find that indirect costs contributed markedly to the total costs associated with both ILD‐SSc and non‐ILD SSc, which is in line with previous cross‐sectional studies on productivity loss associated with SSc that found annual costs from €5500 to €10,500 29–32 . A cohort study from the United States evaluated insured and working SSc cases and matched non‐SSc controls and found excess costs of $3103 (€2736) due to productivity loss in the first year following diagnosis 33 . In a subset cohort from the study, a difference of $5846 (€5155) was found between SSc‐ILD cases ( n = 52) and matched non‐SSc controls during 6 months of follow‐up 12 .…”
Section: Discussionsupporting
confidence: 86%
“…We find that indirect costs contributed markedly to the total costs associated with both ILD‐SSc and non‐ILD SSc, which is in line with previous cross‐sectional studies on productivity loss associated with SSc that found annual costs from €5500 to €10,500 29–32 . A cohort study from the United States evaluated insured and working SSc cases and matched non‐SSc controls and found excess costs of $3103 (€2736) due to productivity loss in the first year following diagnosis 33 . In a subset cohort from the study, a difference of $5846 (€5155) was found between SSc‐ILD cases ( n = 52) and matched non‐SSc controls during 6 months of follow‐up 12 .…”
Section: Discussionsupporting
confidence: 86%
“…The author’s findings complement earlier studies on the epidemic cannibalism of presenteeism over absenteeism on workplace productivity ( 5 , 9 , 10 ) and the potential effect of CTD on labor costs to organizations ( 11 , 12 ). The study underscores that absenteeism and disability costs incompletely gauge the total loss of productivity resulting from CTD-FILD and reminds us about the significance of screening and stopping the detrimental effects of presenteeism on employee patients’ well-being and work engagement before it starts.…”
supporting
confidence: 75%
“…Patients’ reduced direct access to outpatient clinics, in addition to its actual role in reducing the risk of SARS-CoV-2 spreading, may also be an important tool for easing the economic burden of chronic diseases, a matter not to be ignored in the economic crisis we will face due to COVID-19. Telemedicine could be useful in reducing some indirect costs of the rheumatic diseases, like the loss of working days for patients and/or caregivers [ 11 , 12 ], and on the other hand it may favour a more rapid access to the clinic for those urgent and acute conditions that cannot be addressed by telemedicine alone [ 13 ]. Moreover, the use of other available technology resources may increase the continuity of patient monitoring through the use of dedicated apps, and the ability to report day-by-day conditions, symptoms and signs [ 14 ].…”
Section: Discussionmentioning
confidence: 99%